How to fill the working-age population gap in Asia: A population accounting approach - Jong Woo Kang; Grendell Vie Magoncia (Asian Development Bank (ADB), 2016)
The world faces growing challenges of aging populations. Asia is no exception with rapidly increasing life expectancies and falling fertility rates. To help policy makers address these issues, this paper examines three sociopolicy options: (i) extending the retirement age, (ii) augmenting labor migration within the region, and (iii) through using population accounting methodology with the goal of increasing fertility rates. When the retirement age is extended from 65 to 70, the overall dependency ratio in 2050 would decline from 56.7% to 44.7%. If the 2010 dependency ratio were to be maintained, the region would need to import significant numbers of workers aged 15.44 even as those aged 45.64 would be in surplus. India, Pakistan, and the Philippines will be major sources of surplus labor. Raising fertility rates to the 2.1% replacement level will increase the dependency ratio for the time being, but will eventually reduce it over several decades depending on each countryfs demographic structure.
Keywords: J11; J13; J61; 330; demographic shift; dependency ratio; fertility rate; migration; population accounting